2010
DOI: 10.18097/pbmc20105602187
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of pharmacological values of the nifedipine by means of mechanochemical complexation with glycyrrhizic acid

Abstract: A new water-soluble form of the calcium blocker nifedipine (NF) with glycyrrhizic acid (GA) (with molecular ratio 1:4) has been obtained by mechanochemical synthesis. Its pharmacological advantages in comparison with nifedipine were determined. An effective dose of nifedipine in complex reduced to 10 times as compared to its therapeutic dose while high antihypertensive activity preservation and pleiotropic antiarhythmic activity enhancement. This new antihypertensive and antiarhythmic agent (complex of NF:GA =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…The process of complexation was attributed to the multiple noncovalent interactions. After entering the body, glycyrrhizic acid might affect the ordering of lipids and enhance the fluidity and permeability of cell membrane via incorporating and/or extracting the membrane cholesterol, thus promoting the active ingredients penetration into the cell [ [108] , [109] , [110] , [111] , [112] ].…”
Section: Applications Of Supramolecular Assemblies Based On Nsmsmentioning
confidence: 99%
“…The process of complexation was attributed to the multiple noncovalent interactions. After entering the body, glycyrrhizic acid might affect the ordering of lipids and enhance the fluidity and permeability of cell membrane via incorporating and/or extracting the membrane cholesterol, thus promoting the active ingredients penetration into the cell [ [108] , [109] , [110] , [111] , [112] ].…”
Section: Applications Of Supramolecular Assemblies Based On Nsmsmentioning
confidence: 99%
“…Table 1 below shows solubility data reported in [22][23][24][25][26][27][28][29][30][31][32] as far as published for the first time in this review.…”
Section: Synthesis Of Supramolecular Systems Of Water-soluble Polysacmentioning
confidence: 99%
“…If so, whether could this new POD delivery system attenuate the side effects of POD? It has been reported that GA could form the ''host-guest'' type (Polyakov et al, 2006) with some medicines such as nifedipine (Tolstikova et al, 2010), buspirone (Fomina et al, 2014), carotenoids (Polyakov et al, 2006), simvastatin (Vavilin et al, 2008), and lappaconitine (Polyakov et al, 2005), of which GA is the host while the medicine is the guest. Interestingly, it was demonstrated that applications of GA together with these medicines could strengthen their therapeutic actions (Selyutina et al, 2015) and reduce their side effects.…”
Section: Introductionmentioning
confidence: 99%